Teaching teenagers in finance: does it work? - Melanie Lührmann; Marta Serra-Garcia; Joachim Winter (Ludwig-Maximilians-Universität München, Volkswirtschaftliche Fakultät, 2012)
Many initiatives worldwide aim at improving financial literacy through targeted education programs, yet there is little evidence regarding their effectiveness. We examine the impact of a short financial education program on teenagers in German high schools. Our findings reveal that the training program significantly increases teenagers' interest in financial matters and their financial knowledge, especially their ability to properly assess the riskiness of assets. Behaviorally, we observe a decrease in the prevalence of self-reported impulse purchases, but at the same time find no evidence of a significant increase in savings. Our data reveals strong gender differences already before adulthood: Girls show less interest in, and self-assessed knowledge of, financial matters, and are less likely to save.
urn:nbn:de:bvb:19-epub-14101-6
Keywords: C93; D14; 330; Finanzwissen; Weiterführende Schule; Jugendliche; Anlageverhalten; Feldforschung; Deutschland